2008
DOI: 10.1007/s00737-008-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

First Nations women’s mental health: results from an Ontario survey

Abstract: The mental health of Canada's Aboriginal women has received little scholarly attention. This paper describes the mental health of First Nations women living on reserve in Ontario and compares these findings with results from the National Population Health Survey (NPHS). Reserve communities were randomly selected within urban, rural, remote and special access regions. Depression was measured by the Composite International Diagnostic Interview. Alcohol use and health services utilization questions were identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
0
16
0
3
Order By: Relevance
“…38,39 Neither these studies nor ours demonstrated a difference between those with and those without mood and anxiety disorders in terms of the proportion living in a rural area or having Aboriginal status. 38,39 Given that Aboriginal peoples are known to be at greater risk for mental illness, 51,52 and that those living in the territories and persons living on reserves or Crown lands were not included in these studies nor ours, these findings could be a reflection of the underrepresentation of Aboriginal peoples in the population sampled.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…38,39 Neither these studies nor ours demonstrated a difference between those with and those without mood and anxiety disorders in terms of the proportion living in a rural area or having Aboriginal status. 38,39 Given that Aboriginal peoples are known to be at greater risk for mental illness, 51,52 and that those living in the territories and persons living on reserves or Crown lands were not included in these studies nor ours, these findings could be a reflection of the underrepresentation of Aboriginal peoples in the population sampled.…”
Section: Discussionmentioning
confidence: 95%
“…Associations between different factors can be explored; however, causal inferences cannot be drawn from the results due to the survey's cross-sectional design. 55 While the 2014 SLCDC-MA was developed to be nationally representative, the generalizability of the data to the entire Canadian population may be restricted due to the exclusion of the territories and some populations known to be at risk for mental illness, such as Aboriginal peoples 51,52 living on reserves or Crown lands, the homeless, 56 institutionalized patients, 57 and prison residents. 58 The study sample is also limited to Canadians who sought care and received a mood and/or an anxiety disorder diagnosis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Studies that do exist show little difference between rates of substance use in First Nations and non-First Nations populations ( Anderson & McEwan, 2000;MacMillan et al, 2008;Wardman & Khan, 2004). In some cases that have received a great deal of media attention, the rates of substance use in First Nations communities may have been overstated (Wale & Lavoie, 2015).…”
Section: A Critical Examination Of the Prevalence Of Prescription Drumentioning
confidence: 99%
“…Individuals living in the three territories, and some populations known to be at risk for mental illness such as Aboriginal people living on reserves or Crown lands, 52,53 the homeless, 54 institutionalized residents 55,56 and fulltime members of the Canadian Forces 57 were not included. For instance, it is well known that the prevalence of major depression among Canadian seniors living in long-term care facilities is higher (3-4 times) than those living in private dwellings, 55,58 and that the level of disability among those living in correctional facilities is much higher than those living in the community.…”
Section: Strengths and Limitationsmentioning
confidence: 99%